Effects of resistance training on sleep of patients with fibromyalgia: A systematic review - Bastos A.C.R.D.F.* (2023)
© The Author(s) 2023.This study investigated the effects of resistance training (RT) on the sleep quality of patients with fibromyalgia (FM), through a systematic review. The search was carried out in the PubMed, Embase, Scopus, and Web of Science databases. Initially, 148 studies were found, of which six were included for qualitative analysis. Four studies showed significant improvement in sleep after RT. Compared to other exercise modalities, RT proved to be superior to flexibility training and equivalent to aerobic exercise. Interventions lasted from 4 to 21 weeks, the weekly frequency ranged from two to three times, and the intensity ranged from 40% to 80% 1RM, with exercises for the major muscle groups. RT is an intervention that can be used to treat FM, however, more studies are needed to verify its effectiveness in improving sleep.